Optimizing endurance training and performance development in cross-country skiing - Talsnes, R. K. (Nord Universitet, 2020)
Cross-country (XC) skiing is an Olympic Winter sport combining upper-and lower-body work to cross varied terrain in endurance competitions lasting from multiple ~3 min (~1.3-1.8 km) efforts in the sprint discipline to more than 2 hours (=50 km) in the longest distance competitions. Over the last decades, retrospective training analyses of world-class XC skiers combined with more experimental designs have led to a well-developed theoretical framework of endurance training in XC skiing, although there is an ongoing discussion on how training volume and intensity should be progressed throughout the preparation period to optimize performance development. These training methods have elicited some of the highest maximal oxygen uptake (VO2max) values reported in the literature, with concurrent high peak oxygen uptakes (VO2peak) within the main sub-techniques of the skating and classical technique. In this context, it would be interesting to understand how athletes originating from other endurance sports would progress their VO2max/VO2peak values, in addition to improving their technique and efficiency, while transferring to XC skiing and adopting these training methods. Accordingly, the overall objectives of the present dissertation were to: (1) investigate both the short-term and more subsequent effects of increased low (LIT)- vs. high-intensity endurance training (HIT) on performance and physiological adaptations in the preparation period of junior XC skiers (study I-II), and (2) investigate the influence of adopting state-of-the-art training methods in XC skiing to endurance athletes originating from other sports in a talent transfer program (study III-IV). Studies I-II are based on a randomized, experimental design which investigated the effects of increased load of LIT vs. HIT during an 8-week intervention (simulating general preparation period) followed by 5 weeks of standardized training with similar intensity distribution (simulating specific preparation period), and thereafter 14 weeks of self-chosen training and competitions (competition period) in junior XC skiers. Study I demonstrated that performance adaptations, including uphill running time-trial performance and peak speed when incremental running and roller-ski skating to exhaustion in the laboratory, did not differ significantly between the two groups. However, increased HIT elicited ~3-4% greater changes in VO2max running and VO2peak roller-ski skating compared to increased LIT. Study II was a follow-up study, demonstrating that the observed differences in physiological adaptations between the two groups during the 8-week intervention were outbalanced following 5 weeks of standardized training with similar intensity distribution across groups. Lastly, no further changes in any performance or physiological indices neither within nor between groups were found 14 weeks into the subsequent competition period. Studies III-IV are based on a prospective, observational design investigating the development of performance, physiological, and technical indices of endurance athletes (i.e. runners, kayakers, and rowers) transferring to XC skiing during a talent transfer program. Study III demonstrated that the 6-month training period elicited large improvements in sport-specific performance indices (i.e. roller-ski skating and double-poling ergometry), whereas performance indices in a general mode (i.e. running) were unchanged. Improvements in sport-specific performance indices were coincided by better skiing efficiency/work economy and longer cycle lengths while roller-ski skating, as well as increased upper-body one-repetition maximum-strength (1RM) in ski-specific exercises. However, no changes in VO2max running and VO2peak roller-ski skating and double-poling ergometry were found at a group level. Moreover, larger development in sport-specific performance indices were found in runners compared to kayakers/rowers, which coincided with improved VO2peak and overall better physiological adaptations in roller-ski skating. Study IV was a follow-up study, comparing high- and low-performance responders to the 6-month training period using a multidisciplinary approach. Here, high-responders demonstrated superior physiological adaptations both at submaximal and maximal workloads (e.g. power at 4 mmol·L-1 and VO2max running and VO2peak roller-ski skating) than low-responders. These findings were coincided with higher training loads, greater perceived effort during sessions, and lower incidents of injury and illness during the 6-month period in comparison to their lower-responding counterparts. Lastly, qualitative interviews with the athletes coaches highlighted that greater motivation and passion for XC skiing together with the ability to build a strong coach-athlete relationship separated high- from low-responders. Conclusively, the present dissertation demonstrates that performance development can successfully be achieved both by increased low- and high-intensity endurance training during the preparation period in XC skiers, although increased high-intensity training may provide short-term benefits for maximal aerobic energy turnover. However, these different ways of progressing training load had little or no effects on the subsequent performance and physiological development following a period of similar training regimes. Moreover, adopting the theoretical framework of training (i.e. state-of-the-art) in XC skiing on endurance athletes (i.e. runners, kayakers, and rowers) transferring to XC skiing elicits large sport-specific performance improvements, while improvements in aerobic energy turnover were limited. Here, the athletes with largest development had a background from running and the ability to concurrently develop high aerobic energy turnover rates together with skiing efficiency, cycle length, and upper-body specific strength. However, a more long-term approach than employed in the present studies is clearly needed to reach a high international level in XC skiing following talent transfer. Overall, the present data provides novel understanding of both the short-term and more subsequent effects of progressing endurance training volume and intensity in XC skiing, as well as the effects of applying state-of the-art XC skiing training to endurance athletes originating from other sports.